Production of anisotropic SmFe3 magnets by hot deformation - Tetsuji Saito; Yusuke Ogawa; Daisuke Nishio-Hamane (AIP Advances, 2020)
In this study, we investigated the production of anisotropic SmFe3 magnets by the hot deformation of hot-pressed SmFe3 magnets. Hot-pressed SmFe3 magnets were able to be hot-deformed at 973–1073 K into hot-deformed SmFe3 magnets. Although the hot-deformed SmFe3 magnet produced at 973 K was magnetically isotropic, the specimen produced at 1023 K was magnetically anisotropic. The specimen produced at 1073 K was also slightly anisotropic. This indicates that anisotropic SmFe3 magnets were successfully produced by the hot deformation of hot-pressed magnets, as has been reported in the case of hot-deformed Nd-Fe-B magnets. However, the highest coercivity obtained by these anisotropic SmFe3 magnets was only 1.5 kOe, which is insufficient in comparison with rare-earth permanent magnets. Further work is therefore necessary to increase the coercivity of these magnets.